Asuhan Keperawatan Pada Anak Dengan Bronkopneumonia: Suatu Studi Kasus - IGA Dewi Purnamawati; Indria Rifka Fajri (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2020)
Bronchopneumonia is a respiratory disease that causes the highest death to children. Bronchopneumonia can cause impaired gas exchange, airway obstruction, respiratory failure and apnea. The method in this research use approach case of study in children with bronchopneumonia, a sample of one child was given nursing care get the results of the signs and symptoms of bronchopneumonia as fever, ronchi sounds in breathing, loss appetite, cough with thick phlegm and nausea. Nursing problems found in the case of ineffective airway clearance, hypovolemic, deficient nutrition, risk for infection and anxiety in children and parents. The results achieved after carrying out nursing care in children with bronchopneumonia get there is five nursing problems in case. Recommendation: have need of further action nursing care in children order of community provide health education and monitor the nutritional status of children with bronchopneumonia problems.